Lymphocyte subpopulations in donovanosis assessed by monoclonal antibodies and immunoglobulins. - Sehgal, V N (1987)
The haematological profile and peripheral blood lymphocyte subpopulations of 36 patients with donovanosis were estimated by an indirect immunofluorescence technique using monoclonal antibodies. Concentrations of serum immunoglobulins (IgM, IgG, and IgA) were also estimated. The total leucocyte and lymphocyte counts were generally raised, as were total T lymphocyte, T4, and T8 counts. Patients with the hypertrophic variant, however, had decreased numbers of T lymphocytes and T8 cells and increased B cells and IgG. B lymphocyte counts and IgM and IgG concentrations were raised generally.